Activity Guide for Career Education. Middle (Distributed by ERIC Clearinghouse, 1976)
The suggestions for learning activities in career education at the middle level (Grades 6-7) are presented with the aim of establishing career awareness related to five occupational clusters: environmental control, manufacturing, business office, fine arts and humanities, and marine science. The activities are presented under the headings of four domains of career consciousness: self-knowledge and interpersonal skills, knowledge of work and leisure worlds, career planning knowledge and skills, and basic studies and occupational preparation. Activities, resources, and evaluations are presented according to the domain and objectives, showing relationships with academic subject areas for the sixth and seventh grades. A list of occupations within the occupational clusters, a sample interview for Grade 7, local middle school library resources, and resource addresses are appended. (EC)